Jaarboek voor Nederlandse boekgeschiedenis/Yearbook for Dutch Book History 29/2022 Onderwijs en pedagogiek / Education and Pedagogy - Nederlandse Boekhistorische Vereniging, Leiden (Amsterdam University Press, 2022)
Yearbook for Dutch Book History, Volume 29/2022 Education and Pedagogy The Yearbook for Dutch Book History publishes articles in the Dutch and English language on all aspects of the book history of the Low Countries. The central theme of Volume 29 (2022) of the Yearbook is 'Education and Pedagogy'. Contributions to the volume encompass a broad scope. The seventeenth and eighteenth centuries are discussed from the perspectives of Catholic and Protestant schoolbooks, and their roles in contemporary theological disputes, as well as the manner in which the Disaster Year (1672) was canonised in the Nieuwe Spiegel der Jeugd (New Mirror of Youth), which was repeatedly in print between 1674 and 1780. Later periods are treated by contributions detailing handbooks for artists in the nineteenth century and the illustrations of Cornelis Jetses in Bremer schoolbooks. Knowledge and illustrations of the clitoris stand at the heart of a contribution on biological education. The section of thematic articles is concluded by an interview with two publishers of schoolbooks who detail contemporary developments in the schoolbook market. Unrelated to the annual theme, the Yearbook also contains contributions on the printer Peter van Selow and his supposed Dutch background, the survival of editions of the Reformed Liturgy in the later sixteenth and early seventeenth centuries, and an article on so-called Neusboekjes (Nose-books), short comical works from the seventeenth and eighteenth century with pronounced satirical insights into Dutch politics and social norms.